Once-weekly liposomal amphotericin B as Candida prophylaxis in very low birth weight premature infants: A prospective, randomized, open-label, placebo-controlled pilot study - Arrieta, Antonio C.; Shea, Kathy; Dhar, Vijay; Cleary, John P.; Kukreja, Sudeep; Morris, Mindy; Vargas-Shiraishi, Ofelia M.; Ashouri, Negar; Singh, Jasjit (Clinical therapeutics, 2010)
Objective: This study was conducted to evaluate once-weekly liposomal amphotericin B (L-AmB) for Candida prophylaxis in very low birth weight (VLBW) neonates. Methods: This prospective, randomized, open-label, placebo-controlled study included neonates who were <32 weeks’ gestational age, <7 days old, and weighing <1500 g at birth. Subjects were randomized to receive L-AmB 5 mg/kg per week or placebo (dextrose water) and were followed until 6 weeks of age. Surveillance cultures were obtained at baseline, at 72 hours, and weekly thereafter. Study drug was continued until 6 weeks after birth or the discontinuation of high-risk treatments and invasive devices, whichever occurred first. Blood cultures were obtained as clinically indicated. The primary end point was development of Candida colonization by 6 weeks’ postnatal age; secondary end points included development of invasive candidiasis and occurrence of treatment-related adverse events. Safety variables included renal and hepatic function tests, incidence of grade III–IV intraventricular hemorrhage (IVH) and necrotizing enterocolitis (NEC), and mortality. Results: Forty subjects were enrolled and randomized to receive L-AmB (12 males, 8 females; 50% white) or placebo (12 males, 8 females; 35% white). Subjects were evenly distributed by gestational age, age at enrollment, birth weight, race, and sex. Consent was withdrawn after completion of study treatment in 1 subject (L-AmB); 1 subject in each study arm died during the study; and 3 subjects were transferred back to their referring institutions (1 L-AmB, 2 placebo). Thus, 17 subjects in each arm completed all study procedures, although all 40 subjects were evaluable. Colonization before administration of study drug was noted in 4 L-AmB subjects (20%) and 1 placebo subject (5%); 1 (5%) and 3 (15%) subjects in the respective groups developed colonization while receiving study drug. No L-AmB subjects and 1 placebo subject developed candidiasis. One subject in each group died; these deaths were not considered related to study drug or fungal infection. There were no clinical differences between groups in the incidence of grade III–IV IVH, NEC, hypokalemia, nephrotoxicity, need for platelet or packed red blood cell transfusion, or mortality. Conclusions: L-AmB 5 mg/kg once weekly was generally well tolerated in these VLBW infants. The data did not allow evaluation of efficacy. A larger, multicenter, randomized clinical trial of L-AmB for Candida prophylaxis that is appropriately powered is warranted.